The development of receptive skills and its influence on the english learning with students of fourth, fifth, sixth and seventh year of basic education at Manuel José Aguirre Sánchez school, academic year 2012-2013 in the city of Loja - Riofrio Guillin, Andrea Abigail (2014)
The present research work entitled: THE DEVELOPMENT OF RECEPTIVE SKILLS AND ITS INFLUENCE ON THE ENGLISH LEARNING WITH STUDENTS OF FOURTH, FIFTH, SIXTH AND SEVENTH YEARS OF BASIC EDUCATION AT “MANUEL JOSÉ AGUIRRE SANCHEZ” SCHOOL, ACADEMIC YEAR 2012-2013, IN THE CITY OF LOJA has been developed in order to analyze the influence of the receptive skills in the English language Learning. The following methods were used: Descriptive, Analytic in Deductive method to discover, describe, analyze and deduce the obtained information. The data was gathered through a survey applied to the teacher and 117 students. Through an observation sheet, it was evidenced how the teaching-learning of the receptive skills is developed in class and identified the activities and techniques used by the teacher. The researcher carried out the following procedures: tabulation, organization, graphic representation, interpretation, analysis, and hypotheses verification. It was concluded that the development of receptive skills has a significant influence on the English learning of students, because of its natural acquisition; students learn easily the language that is why it is convenient to increase the development of the receptive skills in every English class.